The sympathetic baroreflex is enhanced during emotional stress in rats - Kanbar, Roy (2007)
The sympathetic component of the baroreceptor reflex might play a major role in limiting hypertensive effects of emotional stress. However, it has been suggested that this type of stress inhibits or even suppresses the baroreflex. The aim of the present study was, therefore, to determine the effects of emotional stress on the sympathetic baroreflex in conscious rats. In 11 Sprague Dawley rats, arterial pressure (AP) and renal sympathetic nerve activity (RSNA) were recorded simultaneously before and during exposure to a mild emotional stressor (jet of air). Under both conditions, baroreflex function curves relating AP and RSNA were constructed by fitting a sigmoid function to RSNA and AP measured during sequential nitroprusside and phenylephrine administrations. Air-jet stress significantly (P<0.01) increased the mean levels of AP (from 112 +/- 2 to 124 +/- 2 mmHg), heart rate (from 381 +/- 10 to 438 +/- 18 beats/min) and RSNA (from 0.80 +/- 0.14 to 1.49 +/- 0.23 microV). Sympathetic baroreflex function curves were shifted to a higher level of AP, and this was accompanied by an increase (P<0.01) in the maximum gain (from 9.0 +/- 1.3 to 16.2 +/- 2.1 normalized units (NU)/mmHg). The latter effect was a consequence of an increase (P<0.01) in the maximal range of variations of RSNA (from 285 +/- 33 to 619 +/- 59 NU). Finally, the operating range of the sympathetic baroreflex, which corresponds to the AP range over which the reflex is able to alter RSNA, was increased (from 34 +/- 2 to 41 +/- 3 mmHg; P<0.01). In conclusion, the baroreflex control of RSNA is sensitized and operates over a larger range during emotional stress in rats, which suggests that renal vascular tone, and possibly AP, are very efficiently controlled by the sympathetic nervous system under this condition.